The right to genetic privacy: notes for the construction of a legal regime for the protection of genetic information - Sánchez Montenegro, Juan Pablo (2023)
This article aims to offer some notes to undertake the construction of a legal regime for the protection of genetic information based on the right to genetic privacy. In this sense, we will begin with the definition of genetic information understood as sensitive personal data. Subsequently, genetic information will be presented as an object of protection of the right to genetic privacy, for which an attempt will be made to conceptualize it from Peruvian constitutional doctrine and jurisprudence and the limits of its content (availability) will be developed from the review of the principles contained in Law No. 29733 and Legislative Decree No. 1348, in order to demonstrate their applicability to genetic information.